The mechanisms behind the therapeutic activity of BET bromodomain inhibition - Junwei, Shi (Mol Cell, 2014)
The bromodomain and extra-terminal (BET) protein Brd4 recruits transcriptional regulatory complexes to acetylated chromatin. While Brd4 is considered to be a general transcriptional regulator, pharmacological inhibition of BET proteins shows therapeutic activity in a variety of different pathologies, particularly in models of cancer and inflammation. Such effects have been attributed to a specific subset of downstream target genes, whose expression is disproportionately sensitive to pharmacological targeting of BET proteins. Emerging evidence links the transcriptional consequences of BET inhibition to the association of Brd4 with enhancer elements, which tend to be involved in lineage-specific gene regulation. Furthermore, Brd4 engages in direct regulatory interactions with several DNA-binding transcription factors to influence their disease-relevant functions. Here we review the current understanding of molecular mechanisms that underlie the promising therapeutic effects of pharmacological BET bromodomain inhibition.